Health and safety in digestive endoscopy personnel: a systematic review - Kechagias, Georgios; Riza, Elena; Damikouka, Ioanna; Dounias, George (International Journal of Occupational Safety and Health, 2026)
Introduction: Health professionals face various workplace risks, including infections, improper patient handling, toxic chemicals including high level disinfectants and detergents, radiation, excessive heat and noise, psychosocial hazards, violence and harassment, injuries and inadequate access to safe water and sanitation. The aim of this systematic review was to investigate the occupational health and safety risks for health professionals working in digestive endoscopy departments.Methods: A Systematic Literature Review was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses review method in the PubMed and Scopus databases. The inclusion criteria were used: cross-sectional studies, longitudinal studies, studies published in English, studies published in the last decade (2014-2024), and studies exclusively on endoscopic digestive tract workers.Results: The majority of the review results showed the high prevalence (up to 70%) of musculoskeletal injuries of healthcare professionals associated by the majority of health professionals to their work. The consequences of these injuries are absences from work, needing medical treatment, undergoing physical therapy or surgery. Other occupational hazards included infections and exposure to radiation during procedures with fluoroscopy.Conclusion: Undoubtedly, healthcare professionals working in endoscopic digestive departments are at high risk for occupational injuries and infections. Education of health professionals, at undergraduate level and throughout their professional life, the adoption and implementation of international guidelines and recommendations, while providing appropriate protective equipment, will improve the safety of health professionals and significantly reduce the impact on their health and the functioning of health services.